Percutaneous coronary intervention in diabetic versus non-diabetic patients with prior coronary artery bypass grafting: a propensity score matching study - Ma, Xiaolong (BMC Cardiovasc Disord, 2020)
BACKGROUND: The target of this study was to explore the outcomes of percutaneous coronary intervention (PCI) in diabetic versus non-diabetic patients with prior coronary artery bypass grafting (CABG) surgery. METHODS: Seven hundred and twenty four patients who had previously received CABG and had been treated using PCI combined with drug-eluting stents (DES) between 2009 and 2017 were selected for a retrospective study and allocated into either a diabetes mellitus (DM) or non-diabetes mellitus (No DM) group. A 1:1 propensity score-matched evaluation was conducted and risk adjusted for analysis. The primary outcomes were cardiac death, myocardial infarction, heart failure and revascularization, with a median follow-up duration of 5.13 years. RESULTS: After matching, two-, 5- and 8-year event rate of overall major adverse cardiac events (MACEs) were found to be higher in the DM group (No DM vs DM:15.3, 30.9, 38.5% vs 19.8, 37.8, 52.2%, respectively), although no significant difference was found in the event rate of overall MACEs (hazard ratio [HR]: 1.35; 95% confidence interval [CI]: 1.00 to 1.83 for DM vs No DM; P = 0.052), cardiac death (HR: 0.94; 95% CI: 0.45 to 1.95; P = 0.871), MI (HR: 1.49; 95% CI: 0.95 to 2.32; P = 0.080), HF (HR: 1.54; 95% CI: 0.90 to 2.63 for; P = 0.120) or revascularization (HR: 1.07; 95% CI: 0.72 to 1.59; P = 0.747). Subgroup analysis of PCI in only the NCA showed MACEs (adjusted HR: 1.13; 95% CI: 0.85 to 1.49 for DM vs No DM; P = 0.325), cardiac death (adjusted HR: 0.85; 95% CI: 0.41 to 1.78 for DM vs No DM; P = 0.781), MI (adjusted HR: 1.32; 95% CI: 0.84 to 2.01 for DM vs No DM; P = 0.069), HF (adjusted HR: 1.41; 95% CI: 0.87 to 2.27 for DM vs No DM; P = 0.211) or repeated revascularization (adjusted HR: 0.93; 95% CI: 0.64 to 1.37 for DM vs No DM; P = 0.836). CONCLUSIONS: Compared with non-diabetic patients with prior CABG, subsequent implantation of DES in the native coronary artery of diabetic patients resulted in apparently similar outcomes. TRIAL REGISTRATION: This study was not registered in an open access database.